Renal and Skeletal Anomalies in a Cohort of Individuals With Clinically Presumed Hereditary Nephropathy Analyzed by Molecular Genetic Testing - Stippel, Michaela; Riedhammer, Korbinian M.; Lange-Sperandio, Bärbel; Geßner, Michaela; Braunisch, Matthias C.; Günthner, Roman; Bald, Martin; Schmidts, Miriam; Strotmann, Peter; Tasic, Velibor; Schmaderer, Christoph; Renders, Lutz; et al. (Frontiers in Genetics, 2021)
Background: Chronic kidney disease (CKD) in childhood and adolescence occurs with a median incidence of 9 per million of the age-related population. Over 70% of CKD cases under the age of 25 years can be attributed to a hereditary kidney disease. Among these are hereditary podocytopathies, ciliopathies and (monogenic) congenital anomalies of the kidney and urinary tract (CAKUT). These disease entities can present with a vast variety of extrarenal manifestations. So far, skeletal anomalies (SA) have been infrequently described as extrarenal manifestation in these entities. The aim of this study was to retrospectively investigate a cohort of individuals with hereditary podocytopathies, ciliopathies or CAKUT, in which molecular genetic testing had been performed, for the extrarenal manifestation of SA. Material and Methods: A cohort of 65 unrelated individuals with a clinically presumed hereditary podocytopathy (focal segmental glomerulosclerosis, steroid resistant nephrotic syndrome), ciliopathy (nephronophthisis, Bardet-Biedl syndrome, autosomal recessive/dominant polycystic kidney disease), or CAKUT was screened for SA. Data was acquired using a standardized questionnaire and medical reports. 57/65 (88%) of the index cases were analyzed using exome sequencing (ES). Results: 8/65 (12%) index individuals presented with a hereditary podocytopathy, ciliopathy, or CAKUT and an additional skeletal phenotype. In 5/8 families (63%), pathogenic variants in known disease-associated genes (1x BBS1, 1x MAFB, 2x PBX1, 1x SIX2) could be identified. Conclusions: This study highlights the genetic heterogeneity and clinical variability of hereditary nephropathies in respect of skeletal anomalies as extrarenal manifestation.